Best practice in the management of behavioural and psychological symptoms of dementia - Tible, Olivier Pierre; Riese, Florian; Savaskan, Egemen; von Gunten, Armin (Therapeutic advances in neurological disorders, 2017)
Behavioural and psychological symptoms of dementia (BPSD) occur in most patients with dementia. They cause great suffering in patients and caregivers, sometimes more so than the cognitive and functional decline inherent to dementia. The clinical features of BPSD include a wide variety of affective, psychotic and behavioural symptoms and signs. The causes and risk factors for BPSD are multiple and include biological, psychological and environmental variables. Frequently, their combination, rather than any specific factor, explains the occurrence of BPSD in an individual patient. Thus, a sound etiopathogenetic investigation including the patient and the family or care team is essential. The aim is to develop an individualized treatment plan using a therapeutic decision tree modified by the individual and environmental risk profile. Still, treatment may be difficult and challenging. Clinical empiricism often steps in where evidence from controlled studies is lacking. Psychosocial treatment approaches are pivotal for successful treatment of BPSD. Often a combination of different non-pharmacological approaches precedes drug treatment (most of which is off-label). Regular assessments of the treatment plan and any prescriptions must be carried out to detect signs of relapse and to stop any medicines that may have become inappropriate. Even with optimal management, BPSD will not disappear completely in some cases and will remain challenging for all involved parties. This article is a narrative review based closely on the interprofessional Swiss recommendations for the treatment of BPSD. To establish the recommendations, a thorough research of the literature has been carried out. Evidence-based data were provided through searches of Medline, Embase, ISI and Cochrane-Database research. Evidence categories of the World Federation of Biological Societies were used. Additionally, the clinical experience of Swiss medical experts was considered.